Range Sensing by Stereo Vision of Projected Checker-Patterns - Yuba, Yoshiharu; Hirai, Hiroshi; Ozawa, Satoshi; Tsutsumi, Kiyoshi (The Journal of the Institute of Television Engineers of Japan, 1989)
A Range sensing method based on the binocular stereoscopy of projected checker-patterns is proposed. In this method, a projected checker-pattern is slightly rotated so that only one grid point (i. e., feature point) may lie on each epipolar line of an input image. This setting leads to a simple solution to the stereo-image matching problem. The grid point coordinates on the image plane are evaluated by averaging the coordinates of the neighborhood points, not by pixel units. This evaluation method reduces the effect of coordinate quantization in digital images. Utilizable portions of scenes and errors by one-pixel displacement are discussed. The measurement result of a column is shown. The errors are less than 0.3%. A method for the removal of incorrect correspondence in stereo-image matching is also shown.